Advanced algorithms and data structures - La Rocca, Marcello (Manning Publications, 2021)
An accessible introduction to the fundamental algorithms used to run the world. Richard Vaughan, Purple Monkey Collective As a software engineer, you'll encounter countless programming challenges that initially seem confusing, difficult, or even impossible. Don't despair! Many of these "new" problems already have well-established solutions. Advanced Algorithms and Data Structures teaches you powerful approaches to a wide range of tricky coding challenges that you can adapt and apply to your own applications. Providing a balanced blend of classic, advanced, and new algorithms, this practical guide upgrades your programming toolbox with new perspectives and hands-on techniques. about the technology Can you improve the speed and efficiency of your applications without investing in new hardware? Well, yes, you can: Innovations in algorithms and data structures have led to huge advances in application performance. Pick up this book to discover a collection of advanced algorithms that will make you a more effective developer. about the book Advanced Algorithms and Data Structures introduces a collection of algorithms for complex programming challenges in data analysis, machine learning, and graph computing. You'll discover cutting-edge approaches to a variety of tricky scenarios. You'll even learn to design your own data structures for projects that require a custom solution. what's inside Build on basic data structures you already know Profile your algorithms to speed up application Store and query strings efficiently Distribute clustering algorithms with MapReduce Solve logistics problems using graphs and optimization algorithms about the audience For intermediate programmers. about the author Marcello La Rocca is a research scientist and a full-stack engineer. His focus is on optimization algorithms, genetic algorithms, machine learning, and quantum computing. Easy to follow and filled with practical examples, this book is a fantastic introduction to data structures and algorithms. Zachary Fleischmann, Hawthorne Interactive Look no further if you're looking for a rich book to bridge the stuff of computer science courses and the pragmatic world of software development. George Thomas, Manhattan Associates Teaches how to modify algorithms and data structures to solve practical problems.NARRATED BY JULIE BRIERLEY.